CoVA: An Acuity Score for Outpatient Screening that Predicts Coronavirus Disease 2019 Prognosis. (24th October 2020) - Sun, Haoqi; Jain, Aayushee; Leone, Michael J; Alabsi, Haitham S; Brenner, Laura N; Ye, Elissa; Ge, Wendong; Shao, Yu-Ping; Boutros, Christine L; Wang, Ruopeng; Tesh, Ryan A; Magdamo, Colin; et al.
Abstract: Background: We sought to develop an automatable score to predict hospitalization, critical illness, or death for patients at risk for coronavirus disease 2019 (COVID-19) presenting for urgent care. Methods: We developed the COVID-19 Acuity Score (CoVA) based on a single-center study of adult outpatients seen in respiratory illness clinics or the emergency department. Data were extracted from the Partners Enterprise Data Warehouse, and split into development (n = 9381, 7 March–2 May) and prospective (n = 2205, 3–14 May) cohorts. Outcomes were hospitalization, critical illness (intensive care unit or ventilation), or death within 7 days. Calibration was assessed using the expected-to-observed event ratio (E/O). Discrimination was assessed by area under the receiver operating curve (AUC). Results: In the prospective cohort, 26.1%, 6.3%, and 0.5% of patients experienced hospitalization, critical illness, or death, respectively. CoVA showed excellent performance in prospective validation for hospitalization (expected-to-observed ratio [E/O]: 1.01; AUC: 0.76), for critical illness (E/O: 1.03; AUC: 0.79), and for death (E/O: 1.63; AUC: 0.93). Among 30 predictors, the top 5 were age, diastolic blood pressure, blood oxygen saturation, COVID-19 testing status, and respiratory rate. Conclusions: CoVA is a prospectively validated automatable score for the outpatient setting to predict adverse events related to COVID-19 infection. Abstract : A coronavirus disease 2019 (COVID-19) outpatient screening score is developed and validated prospectively in a single-center setting. It predicts 7-day prognosis: hospitalization, intensive care/ventilation, or death, based on 30 predictors including demographics, COVID-19 status, vital signs, radiology report, and medical history.